Pengaruh Lingkungan Sosial, Kepercayaan Merek, dan Citra Merek Terhadap Keputusan Pembelian (Studi Kasus pada pengguna iPhone di Kota Bogor) - Fadillah, Adil; Tifani, Novia (LPPM Institut Bisnis dan Informatika Kesatuan, 2018)
The purpose of this study were (1) to determine the influence of social environment on purchasing decisions of iPhone, (2) to determine the effect confidence brand on purchase decisions of iPhone users,(3) to determine the effect of brand image to purchasing decisions of iPhone (4) to determine the influence of social environment, brand trust and brand image altogether on purchasing decisions of iPhone. The respondents in this research were 100 respondents, taken from the iPhone smartphone users in the city of Bogor and the campus STIE Kesatuan. The data were then processed using SPSS, 2016. From the analysis conducted, following results were obtained; (1) The social environment has a positive influence on purchase decisions resulted in a coefficient of 0.056 and a significance value of 0.247. (2) Trust brand has a positive influence on purchase decisions resulted in a coefficient of 0.257 and a significance value of 0.004. (3) The influence of brand image has a positive influence on purchase decisions resulted in a coefficient of 0.251 and a significance value of 0.002. (4) Social Environment, Brand Trust and Brand altogether have positive influence and significance on purchasing decisions of iPhone smartphones with significant value 0,000. Detreminasinya coefficient value of 0.369 indicates that 36.9% Social Environment variables, Brand Trust and Brand Purchase Decisions influencing variables, whereas for 63.1% explained by other variables not examined in this study